PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA KERJA MELALUI MOTIVASI BERPRESTASI SEBAGAI VARIABEL MEDIASI TERHADAP KINERJA GURU DI SMK NEGERI 5 KENDAL - Eko Hery Saputro; Inaya Sari Melati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of transformational leadership and work culture on teacher performance, both directly and indirectly, through achievement motivation as a mediating variable at SMK Negeri 5 Kendal. The primary background of this research is the low results of national teacher performance evaluations and the fluctuation of teacher performance scores at the research site.The research method employed is a quantitative approach with inferential statistical analysis techniques. Data were collected through questionnaires that had been tested for validity and reliability. The population of this study consisted of teachers at SMK Negeri 5 Kendal. Data analysis was conducted using multiple linear regression and the Sobel Test to examine the mediation effect, assisted by SPSS software.The results of the study indicate that transformational leadership has a significant effect on teacher performance. Better implementation of transformational leadership by the school principal is followed by an increase in teacher performance. Work culture was also found to have a strong direct influence on the quality of teacher performance. However, the Sobel Test results showed that achievement motivation was not a significant mediating variable in the relationship between transformational leadership or work culture and teacher performance. This indicates that at SMK Negeri 5 Kendal, work environment factors and leadership styles provide a more dominant direct impact compared to individual internal motivational drives. This study recommends strengthening work culture and leadership as priority steps to effectively improve teacher performance.